Changes in the Perception of School Climate among Brazilian High School Students Between 2001 and 2011 - Sofia Wolker Manta; Kelly Samara da Silva; Cassiano Ricardo Rech; Bruno Goncalves Galdino da Costa; Tayna Iha; Adair da Silva Lopes; Markus Vinicius Nahas (Shiraz University of Medical Sciences, 2017)
Background: Perception school climate has been investigated for contributing to health promotion policies and education in the school environment. In low- and middle-incomes countries, tracking information with respect to these perceptions are still scarce. Objectives: To analyze the changes in the perception of adolescents on the school climate during the course of a decade in the state of Santa Catarina, in southern Brazil. Methods: Two cross-sectional surveys were conducted in 2001 (n = 5.028) and 2011 (n = 6.529) among public high school students (15 to 19 years old). Factors related to the negative perception of the school climate were evaluated using a structured questionnaire. Results: After ten years, there were significant differences in the proportion of adolescents who had a negative perception of the time spent in school (from 3.1% to 16.3%), of their relationship with peers (from 3.0% to 13.5%), and their relationship with teachers and staff (from 2.9% to 7.2%). Conclusions: Students reported having a worse perception of the school social environment. Interventions that encourage the adoption and maintenance of positive social relationships and healthy habits are needed in the school community.